Cancer‐associated fibroblasts predict poor outcome and promote periostin‐dependent invasion in oesophageal adenocarcinoma. Issue 3 (February 2015) - Underwood, Timothy J; Hayden, Annette L; Derouet, Mathieu; Garcia, Edwin; Noble, Fergus; White, Michael J; Thirdborough, Steve; Mead, Abbie; Clemons, Nicholas; Mellone, Massimiliano; Uzoho, Chudy; Primrose, John N; et al.
Abstract Interactions between cancer cells and cancer‐associated fibroblasts (CAFs) play an important role in tumour development and progression. In this study we investigated the functional role of CAFs in oesophageal adenocarcinoma (EAC). We used immunochemistry to analyse a cohort of 183 EAC patients for CAF markers related to disease mortality. We characterized CAFs and normal oesophageal fibroblasts (NOFs) using western blotting, immunofluorescence and gel contraction. Transwell assays, 3D organotypic culture and xenograft models were used to examine the effects on EAC cell function and to dissect molecular mechanisms regulating invasion. Most EACs (93%) contained CAFs with a myofibroblastic (α‐SMA‐positive) phenotype, which correlated significantly with poor survival [p = 0.016; HR 7. 1 (1.7–29.4)]. Primary CAFs isolated from EACs have a contractile, myofibroblastic phenotype and promote EAC cell invasion in vitro (Transwell assays, p ≤ 0.05; organotypic culture, p < 0.001) and in vivo (p ≤ 0.05). In vitro, this pro‐invasive effect is modulated through the matricellular protein periostin. Periostin is secreted by CAFs and acts as a ligand for EAC cell integrins αvβ3 and αvβ5, promoting activation of the PI3kinase–Akt pathway. In patient samples, periostin expression at the tumour cell–stromal interface correlates with poor overall and disease‐free survival. Our study highlights the importance of the tumour stroma in EAC progression. Paracrine interaction between CAF‐secreted periostin and EAC‐expressed integrins results in PI3 kinase–Akt activation and increased tumour cell invasion. Most EACs contain a myofibroblastic CAF‐rich stroma; this may explain the aggressive, highly infiltrative nature of the disease, and suggests that stromal targeting may produce therapeutic benefit in EAC patients. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.